Application of UNIDROIT Principles in International Trade Contracts in Indonesia - Riyandi Fatur Nugraha; Yuni Dhea Utari; Kheqal Fitra Dinata; Muhammad Fadhli (Penerbit Hellow Pustaka, 2024)
This research explains the application of UNIDROIT principles in international trade contracts in Indonesia. This research uses normative legal methods, which examine the legal principles written in statutory regulations. The UNIDROIT principles, which are considered global guidelines in international private law, are used as a framework in this research. The research results show that UNIDROIT principles, such as freedom of contract, good faith and compliance, legal certainty, contract formation, obligations of the parties, dispute resolution, have played an important role in creating a stable and reliable legal environment in international trade contracts in Indonesia . These principles help increase trust between parties involved in cross-border trade transactions and facilitate the resolution of disputes in a peaceful and efficient manner. from this research, it can be concluded that the application of UNIDROIT principles has provided great benefits for business people in Indonesia, both in terms of increasing legal certainty and facilitating sustainable international trade. However, to maximize the benefits of implementing UNIDROIT principles, concrete steps are needed such as ratification of the UPICCs, adjustments to national contract law, and strengthening of legal infrastructure. Thus, this research provides a comprehensive view of the importance of applying UNIDROIT principles in the context of international trade contracts in Indonesia.